Designing Correspondence Administration Information Systems Using User Experience Design Model - Eric Alfonsius (Jurnal Ilmiah Informatika dan Ilmu Komputer (JIMA-ILKOM), 2022)
The design of the community service correspondence information system application starts from the data collection method (interviews, observations and documentation) using a user centered design model has 5 stages, namely Empathized, Define Problem Statements, Indentation, and Prototype in accordance with user needs in community service correspondence administration information systems that can overcome existing problems. The results of ISO 25010 testing that has been carried out involving respondents that the resulting software feasibility quality conclusion has a percentage of success with an average total of 95.92%.